Association of Psychiatrists in Africa 1974 workshop : alcoholism and drug addiction - International Council on Alcohol and Addictions (Lausanne : International Council on Alcohol and Addiction, 1974)
Hoe worden alcoholisme en drugsverslaving aangepakt in Afrika?